Overview of edible bird's nests and their contemporary issues - Jamalluddin, Nurul Hidayah; Tukiran, Nur Azira; Fadzillah, Nurrulhidayah; Fathi, Sharihan (Elsevier, 2019)
Edible bird's nest (EBN) is a traditional Chinese cuisine that attracts numerous attentions at the local point of view extending to worldwide level. Huge demand from EBN enables it to secure name labels among different types of other foodstuffs, which were found to be rich with carbohydrate, protein and amino acid. Today, EBN has been used as ingredients in cosmetics and pharmaceutical products. Malaysia is the world's third largest supplier of EBN after Thailand and Indonesia. Therefore, the government included certain initiatives in order to comply with several laws and standards as fundamental guidelines. Currently, contemporary EBN issues are becoming a pandemic in this industry and create chaos for consumers and operators. The issues include adulterations, banning, integrity of halal and haram, allergic reactions and heavy metal intoxication. The researchers identified several approaches in order to detect and authenticate EBN using advanced technologies and high-end instrumentations. The approaches were improved by certain chemometric analysis, which produces convincing and reliable data. Current situation and future views of EBN are also discussed in the study.